DEM simulations and experiments investigating the influence of feeding plate angle in a rubber-roll paddy grain huller. (January 2021) - Chen, Peiyu; Han, Yanlong; Jia, Fuguo; Meng, Xiangyi; Xiao, Yawen; Bai, Shigang
Abstract : The orientation of paddy grains during hulling is one of the main factors that determines the one-time hulling ratio and breakage ratio during processing with rubber rollers. Understanding the adjustment mechanism of paddy grain orientation angle in feeding process is the key to controlling the orientation angle, but the mechanisms involved remain poorly understood. The feeding process using an inclined plate feeder was simulated using the discrete element method (DEM). The effect of the inclination angle of the long feeding plate was analysed and the requirements for an adjustment mechanism were clarified. The results showed that the uniformity of inclination angle of paddy grains decreased with the increasing inclination angle for the long feeding plate. The results showed that the regular movements of paddy grains were controlled by shear action of paddy grain flow. The depth of the grain layer determines the distribution of paddy grain orientation angle. This study could provide guidance for the design and optimisation of feeding systems and help understand the adjustment mechanism requirements for orientating non-spherical grains in grain flow Highlights: Adjustment mechanisms of orientation angle of paddy grain examined numerically. Paddy grains rotate around one of their vertices. Regular rotational motion is caused by the shear action of the grain flow. Number of flow layer determines the change of orientation angle. Regular rotational movements can align orientation angle to flow direction.